Sedimentology and geomorphology analysis of coastal area along pantai penarik, terengganu before and during northeast monsoon season - Ku Yusoff, T.A.I. (Institute of Physics Publishing, 2017)
This research is conducted to understand the sedimentology and morphological change before and during the northeast monsoon at the east coast of peninsular Malaysia. The increase in wind speed, wave energy and rainfall during the northeast monsoon are believed to causes the coastal erosion to increase during the season. Rapid development along the east coast area might disrupt the sediments distribution which can increase the coastal erosion rate every year. The understanding on the sediments distribution, erosion and deposition as well as the morphological change can help to figure out if the coastal erosion can affect the infrastructure in the future. The result of the study can show the necessity to perform mitigation or any required action toward the problem that might happen. © Published under licence by IOP Publishing Ltd.